PERSONAL CHARACTERISTICS AND TRAINING OPPORTUNITIES AS DETERMINANTS OF ORGANISATIONAL COMMITMENT AMONG NIGERIA NATIONAL PARKS’ EMPLOYEES - Adekunle Anthony Ogunjinmi; Samuel Akinyele Onadeko; Olugbenga Jelili Ladebo; Kehinde Oluwaseye Ogunjinmi (European Scientific Journal, ESJ, 2014)
This study aimed at exploring linkages between employees’ personal characteristics, training opportunities and organisational commitment. The study population was the employees of seven national parks in Nigeria. Collection of data was through the use of questionnaire. Also, 231 employees were randomly selected from all the parks, representing 11.6% of the total population of the employees. Data obtained were subjected to descriptive and inferential analyses such as Pearson’s Correlation and multiple linear regression. Majority of the respondents were male (88.7%) with the median age of 35 years. The employees had high training opportunities. They however had generally low level of organisational commitment. Significant difference exists in the employees’ organisational commitment based on gender, age, and work experience. There was significant but weak correlations between organisational commitment and training opportunities while gender, age and education were the determinants of organisational commitment. The study confirmed the significance of personal factors as determinants of organisational commitment. Gender, age and education were confirmed as the determinants of organisational commitment. For a more comprehensive understanding of other possible determinants and antecedents of organisational commitment of nature conservation organisations’ employees, further studies should include more factors in analytical model.